Tribological investigation of ultra-high molecular weight polyethylene against advanced ceramic surfaces in total hip joint replacement - Choudhury, D.; Roy, T.; Krupka, I.; Hartl, M.; Mootanah, R. (Proceedings of the Institution of Mechanical Engineers Part J-Journal of Engineering Tribology, 2015)
The aim of the study was to investigate whether a modified ceramic head surface could reduce the friction and wear rate of simulated ceramic-on-polyethylene hip joints. To address this aim, ultra-high molecular weight polyethylene (UHMWPE) was made to slide on aluminium oxide (Al2O3), dimpled Al2O3, diamond-like carbon (DLC) coated and DLC-coated dimpled substrates. The experiment condition was replicated to simulate artificial hip joints in terms of contact pressure, speed and temperature. UHMWPE on non-dimpled Al2O3 showed lower friction coefficient and wear rate compared to other advanced surfaces. Lower wettability, and higher hardness and surface adhesion of DLC resulted in increased friction and wear. The high difference in modulus of elasticity and hardness between UHMWPE and both, Al2O3 and DLC, reduced the effectiveness of textured surface techniques in friction and wear reduction. Therefore, no tribological benefit was found by fabricating either DLC coating or surface texturing on hard surface when rubbed against softer UHMWPE.